Past, Present and Future Status of the Mollusca of the Upper Tombigbee River - Henry van der Schalie (Hello World!, 1981)
Studies of the mollusks of Alabama drainages (including rivers such as the Tombigbee flowing through Mississippi) were undertaken at the turn of the century over an extended period by a group of well-known malacologists. Their work was sponsored largely by Dr. Bryant Walker, a wealthy lawyer who developed an international reputation as a malacologist; in the museum built in back of his Detroit home he amassed a collection of about 100,000 lots.